ANALISA DAN PERANCANGAN SISTEM INFORMASI PENGAJUAN KREDIT PENSIUN DI BANK BTPN KANTOR CABANG MAJALAYA - Suwartika K, Rini; Hermas, Rika (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2019)
The research was aimed to know the process of current system and also design and develop submission of pension credit information system design at BTPN branch office Majalaya. The research method used were done by direct observation, interview, and also literature study. Based on the research result, the process of current system is still manual is the Lorina Menu, so it is less effective and efficient. The software development method used was using waterfall method and the design tool was UML (Unified Modeling Language), Delphi as language program and SQL Server as database system. There are some suggestion for solving those problems: 1) maximaxing technology usage; 2) making system maintenance routinely: 3) providing training for users of the application system; and 4) developing system in future.